Advances in teacher education - McClelland, V.Alan.; Varma, Ved P. (London : Routledge, 2012)
During the 1980s, Britain's educational system was restructured and redirected. Of the many changes which were made, perhaps the most far-reaching have affected the education of teachers themselves. The contributors to this book have all been centrally involved in the reforming process of teacher education, as providers, assessors, or practitioners, and it is as such that they reflect upon the significant features of the changes in teacher education, while assessing the fulfilment of the initial promise. The book analyses recent advances in teacher education, especially the trend towards imp
Includes bibliographical references and index.
Keywords: Teachers -- Training of -- Great Britain; EDUCATION -- Research